Regio‐ and Stereoselective Cascade of β, γ‐Unsaturated Ketones by Dipeptided Phosphonium Salt Catalysis: Stereospecific Construction of Dihydrofuro‐Fused [2, 3‐b] Skeletons. (3rd August 2021) - Zhang, Hongkui; He, Jiajia; Chen, Yayun; Zhuang, Cheng; Jiang, Chunhui; Xiao, Kai; Su, Zhishan; Ren, Xiaoyu; Wang, Tianli
Abstract: Chiral (dihydro)furo‐fused heterocycles are significant structural motifs in numerous natural products, functional materials and pharmaceuticals. Therefore, developing efficient methods for preparing compounds with these privileged scaffolds is an important endeavor in synthetic chemistry. Herein, we develop an effective, modular method by a dipeptide‐phosphonium salt‐catalyzed regio‐ and stereoselective cascade reaction of readily available linear β, γ‐unsaturated ketones with aromatic alkenes, affording a wide variety of structurally fused heterocyclic molecules in high yields with excellent stereoselectivities. Moreover, mechanistic investigations revealed that the bifunctional phosphonium salt controlled the regio‐ and stereoselectivities of this cascade reaction, particularly proceeding through the initial ketone α‐addition followed by O ‐participated substitution; and the multiple hydrogen‐bonding interactions between Brønsted acid moieties of catalyst and nitro group of aromatic alkene were crucial in asymmetric induction. Given the generality, versatility, and high efficiency of this method, we anticipate that it will have broad synthetic utilities. Abstract : A highly regio‐, diastereo‐ and enantioselective cascade reaction of β, γ‐unsaturated carbonyl compounds with 2‐nitroindoles, 2‐nitrobenzofurans and 2‐nitrobenzothiophenes was achieved through dipeptide‐phosphonium salt catalysis. Three types of structurally fused heterocycles were obtained in excellent stereoselectivities. Regioselectivities were determined by the low reaction energy resulting from the initial α‐addition but not γ‐addition.